PENDIDIKAN KESEHATAN TENTANG PERILAKU MENYIMPANG PADA KADER REMAJA - Sumiatin, Titik; Wahyu Tri Ningsih; Su'udi; Moch. Bahrudin; Tanty Wulan Dari; Siti Maimuna (Jurnal Abdi Masyarakat, 2024)
The increasing rate of juvenile delinquency is very worrying for many parties. Both related to mass fights, drugs, premarital sexual relations, drinking and so on. Even though various efforts have been made, until now the incidence rate is still difficult to reduce. The forum for activities provided to teenagers, such as the Youth Posyandu, the formation of youth cadres is still not running optimally. The aim of this community service is to optimize the knowledge of juvenile cadres through health promotion and discussions on juvenile delinquency. The method used through interactive discussions about juvenile delinquency (deviant behavior). The results of this community service activity are that the knowledge of teenage after health education and interactive discussions is mostly very good. Adolescent health education activities are felt by youth cadres to be very beneficial, the cadres really want this activity not to stop here, but to continue